Observational Coding Systems of Parent–Child Interactions During Painful Procedures: A Systematic Review. Issue 1 (4th June 2017) - Bai, Jinbing; Swanson, Kristen M.; Santacroce, Sheila J.
Abstract: Background: Parent interactions with their child can influence the child's pain and distress during painful procedures. Reliable and valid interaction analysis systems (IASs) are valuable tools for capturing these interactions. The extent to which IASs are used in observational research of parent‐child interactions is unknown in pediatric populations. Objectives: To identify and evaluate studies that focus on assessing psychometric properties of initial iterations/publications of observational coding systems of parent‐child interactions during painful procedures. Methods: To identify and evaluate studies that focus on assessing psychometric properties of initial iterations/publications of observational coding systems of parent‐child interactions during painful procedures. Computerized databases searched included PubMed, CINAHL, PsycINFO, Health and Psychosocial Instruments, and Scopus. Timeframes covered from inception of the database to January 2017. Studies were included if they reported use or psychometrics of parent‐child IASs. First assessment was whether the parent‐child IASs were theory‐based; next, using the Society of Pediatric Psychology Assessment Task Force criteria IASs were assigned to one of three categories: well‐established, approaching well‐established, or promising. Results: A total of 795 studies were identified through computerized searches. Eighteen studies were ultimately determined to be eligible for inclusion in the review and 17 parent‐child IASs were identified from these 18 studies. Among the 17 coding systems, 14 were suitable for use in children age 3 years or more; two were theory‐based; and 11 included verbal and nonverbal parent behaviors that promoted either child coping or child distress. Four IASs were assessed as well‐established; seven approached well‐established; and six were promising. Conclusions: Findings indicate a need for the development of theory‐based parent‐child IASs that consider both verbal and nonverbal parent behaviors during painful procedures. Findings also suggest a need for further testing of those parent‐child IASs deemed "approaching well‐established" or "promising".